Primary Adrenal Tumors in Bitches - Maiara Goltara; Ágatha Silva Veroneze; Cleber Dalmaschio Filho; Julia Gabriela Vieira Giurizatto; Lunanda Vago de Oliveira; Séfora Vieira da Silva Gouvêa de Barros; Pereira, Clairton Marcolongo; Jéssica Miranda Cota (Acta Scientiae Veterinariae, 2025)
Background: Adrenal tumors are rare in dogs, accounting for less than 2% of diagnosed neoplasms. They can be primary or metastatic, and are classified as adrenocortical or medullary based on their histological origin. Functional tumors secrete hormones, leading to clinical signs, such as polyuria, polydipsia, and abdominal distension. Adrenalectomy is the primary treatment but carries perioperative risks. This study reports 3 cases of adrenal tumors, highlighting their clinical presentation, diagnostic approaches, surgical outcomes, and histopathological findings. Cases: Case 1. A 11-year-old bitch Shih Tzu presented with polyuria, polydipsia, polyphagia, and mammary lump. Ultrasonography and CT revealed a nodular mass in the left adrenal gland. A low-dose dexamethasone suppression test suggested cortisol-secreting adrenal-dependent hyperadrenocorticism. The dog underwent adrenalectomy without complications, and histological examination confirmed adrenocortical adenoma. The patient remained disease-free for two years postoperatively. Case 2. A 7-year-old neutered bitch Dalmatian underwent routine imaging, which revealed an incidental adrenal mass. Ultrasound and CT showed a left adrenal nodule without vascular invasion or thrombus formation. Hormonal tests were used to exclude functional diseases. The bitch underwent an adrenalectomy without complications. The histopathological findings confirmed nodular adrenocortical hyperplasia. No tumor recurrence was observed over the 3-years follow-up period. Case 3. A 15-year-old neutered bitch mixed-breed dog presented with vomiting, hyporexia, and diarrhea. Imaging revealed a large right adrenal mass in close contact with major vessels, causing vena cava displacement. Dexamethasone suppression test ruled out cortisol overproduction. The bitch underwent adrenalectomy, and histological examination confirmed the diagnosis of adrenocortical carcinoma. The patient was followed-up for 3 months without evidence of recurrence. Discussion: All 3 bitches underwent adrenalectomy without perioperative complications, supporting studies linking surgery to prolonged survival. No recurrence was observed during the long-term follow-up, suggesting favorable outcomes in selected cases. All patients were females, which is consistent with reports of higher adrenal tumor incidence in spayed bitches. Their ages ranged from 7 to 15 years, which is consistent with the literature. A slight left adrenal predilection was noted, although the prognosis depended more on factors such as vascular invasion, particularly of the caudal vena cava, which complicates surgery. In Case 3, tumor proximity to the pancreas raised concerns about pancreatitis, reinforcing the need for thorough preoperative evaluation. Ultrasound and CT are essential for diagnosis and surgical planning. While ultrasound has moderate sensitivity, CT provides better details, especially for assessing vascular invasion and tumor extent. Large irregular lesions are often indicative of malignancy. Two cases involved incidental adrenal masses ("incidentalomas"), highlighting the need for hormonal assessment as some tumors may be functional despite no clinical signs. In Case 1, hormonal testing confirmed hypercortisolism, justifying adrenalectomy. Histopathology confirmed adenoma in Case 1 and carcinoma in Case 3. Carcinomas typically exceed 2 cm, with capsular invasion, necrosis, and hemorrhage, while adenomas show cytoplasmic vacuolization. Nodular adrenocortical hyperplasia, observed in Case 2, is common in older dogs without a clear cause, although its link to adenohypophyseal proliferation was not observed here. These cases emphasize the importance of imaging, hormonal testing, and histopathology in the diagnosis of adrenal tumors. Despite these risks, adrenalectomy remains a viable treatment, with favorable long-term outcomes in well-selected cases. Keywords: Adrenal tumor, adrenalectomy, canine neoplasia, imaging diagnosis, histopathology.